APLIKASI PENGENALAN PLANET PADA TATA SURYA BERBASIS AUGEMENTED REALITY - Indrawan Gustha Wisesha; Ikrimach Ikrimach (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
The use of Information Technology (IT) in the process of conveying information about the world of education is experiencing rapid development. Currently, the newest technology used to convey information is Augmented Reality (AR) technology. In AR technology, users can visualize objects in 3 dimensions. AR has the advantage of being interactive and real time so that AR is widely implemented in various fields, especially in the field of education. In the world of education, AR is used as a medium to introduce the planets in the solar system. The aim of this report is to review the use of AR technology in introducing elementary school students to the planets in the Solar System. Based on the results of a review of several journals relevant to AR research, information was obtained that AR technology can be used as a medium to introduce planets in the solar system to elementary school students. In making AR applications, the methods used can use Marker Based Tracking and Markless AR methods.